Budaya Behavioral Integrity Pada Lingkungan Kerja - Rini Mutianisa; Anniez Rachmawati Musslifa (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The gap between awareness of integrity in business and lowering standards of behavior is growing. The implication is that the attribute of integrity is only given to individuals with morality that conforms to societal standards. However, assigning the attribute of integrity does not always require moral approval. This research aims to analyze the influence of a culture of behavioral integrity on the work environment. The results of this research can be used as a reference and reference regarding behavior integrity in the work environment. This research uses library research methods. The results of the discussion concluded that a culture of behavioral integrity had a positive and significant effect on performance at several institutions. A behavioral culture of integrity also has a significant influence on company performance. Integrity in the workplace has benefits such as maintaining integrity, reducing stress, increasing job satisfaction, and building a positive organizational culture for employee development.